Employee Retention Policy as HR Best Practice and Organisation Performance - Ekanem, Ekanem Daniel; Osarenmwinde, Smart (NIU Journal of Social Sciences, 2025)
This study examined the impact of employee retention policies as a human resource best practice on organizational performance, using the University of Benin Teaching Hospital (UBTH) as a case study. The focus was on two key components of retention policies, including competitive compensation and benefits, and career succession development programs. Using Taro Yamane formula, a sample size of three hundred and sixty (366) was arrived out, however, on distribution of the research questionnaire only 360 was found usable for this study. Data was collected through structured questionnaires. The analysis utilized both descriptive statistics such as (frequency, mean, and percentage) and inferential statistics such as (regression analysis) to evaluate the relationships between various variables used. The findings revealed that competitive compensation significantly enhance organizational performance. Conversely, career succession development was found to have no significant effect. Based on these findings, the study recommends that improving compensation packages, while reevaluating and redesigning career development initiatives to support the achievements of organizational goals and also to meet employee expectations. Keywords: Employee Retention, Organizational Performance, Competitive Compensation, Career Succession Development.